2016
DOI: 10.25006/ia.4.s2-a18.75
|View full text |Cite
|
Sign up to set email alerts
|

TAAR1 modulates cortical glutamate NMDA receptor function

Abstract: Trace Amine-Associated Receptor 1 (TAAR1) is a G protein-coupled receptor expressed in the mammalian brain and known to influence subcortical monoaminergic transmission. Monoamines, such as dopamine, also play an important role within the prefrontal cortex (PFC) circuitry, which is critically involved in high-o5rder cognitive processes. TAAR1-selective ligands have shown potential antipsychotic, antidepressant, and pro-cognitive effects in experimental animal models; however, it remains unclear whether TAAR1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 38 publications
(55 reference statements)
1
18
0
Order By: Relevance
“…As previously described, TAAR1 agonists can overcome both the hyperlocomotion and cognitive impairments induced by administration of NMDA receptor antagonists (Revel et al, 2011(Revel et al, , 2013. That TAAR1 can regulate glutamatergic transmission is further suggested by the significant alterations in glutamate transmission found in the prefrontal cortex of TAAR1-KO mice (Espinoza et al, 2015b), a location where TAAR1 mRNA is found in wild-type mice. Application of a patch-clamp electrophysiological approach to cortical slices revealed deficient glutamate NMDA receptor function in prefrontal cortex layer V pyramidal neurons of TAAR1-KO mice (Espinoza et al, 2015b).…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 62%
See 3 more Smart Citations
“…As previously described, TAAR1 agonists can overcome both the hyperlocomotion and cognitive impairments induced by administration of NMDA receptor antagonists (Revel et al, 2011(Revel et al, , 2013. That TAAR1 can regulate glutamatergic transmission is further suggested by the significant alterations in glutamate transmission found in the prefrontal cortex of TAAR1-KO mice (Espinoza et al, 2015b), a location where TAAR1 mRNA is found in wild-type mice. Application of a patch-clamp electrophysiological approach to cortical slices revealed deficient glutamate NMDA receptor function in prefrontal cortex layer V pyramidal neurons of TAAR1-KO mice (Espinoza et al, 2015b).…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 62%
“…That TAAR1 activation acutely regulates the glutamatergic system was supported by the observation that cultured cortical neurons treated with the TAAR1 agonist RO5166017 showed a modest increase in GluN1 expression and a significant increase in the phosphorylation of the Ser 896 residue (Espinoza et al, 2015b). Furthermore, TAAR1 expression was mapped to layer V cortical neurons in TAAR1-KO/dsRed knock-in rats, a recently developed transgenic rat model in which the fluorescent marker dsRed is expressed under the control of the TAAR1 promoter (Espinoza et al, 2015b). Since many cortical neurons in layer V project to the striatum, these data suggest that TAAR1 may modulate corticostriatal 594 glutamatergic transmission.…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 94%
See 2 more Smart Citations
“…Trace amine-associated receptor 1 (TAAR1) is a relatively recently discovered G protein-coupled receptor (Borowsky et al, 2001;Bunzow et al, 2001), which is expressed in monoaminergic brain regions and throughout the limbic system (Borowsky et al, 2001;Lindemann et al, 2008;Espinoza et al, 2015). TAAR1 is thought to play a role in regulating the limbic network, reward circuits, cognitive processes, and mood states and has been proposed as a pharmacological target for the treatment of mental disorders (Wolinsky et al, 2007;Lindemann et al, 2008;Miller, 2011;Revel et al, 2013) and psychostimulant dependence (Di Cara et al, 2011;Pei et al, 2014;Cotter et al, 2015;Jing and Li, 2015).…”
Section: Introductionmentioning
confidence: 99%